Current-Based Coordination of Distributed Energy Resources in a Grid-Connected Low-Voltage Microgrid: An Experimental Validation of Adverse Operational Scenarios - Alonso, Augusto M. S.; Arenas, Luis De Oro [UNESP]; Brandao, Danilo; Tedeschi, Elisabetta; Machado, Ricardo Q.; Marafao, Fernando P. [UNESP] (Mdpi, 2022)
Low-voltage grid-connected microgrids rely on the exploitation of inverter-interfaced distributed energy resources (DERs) in order to feed loads and to achieve bidirectional power flow controllability at their point of common coupling (PCC) with the upstream grid. However, adverse operational conditions, such as the existence of DERs of different operation natures, DERs of non-equal power ratings, as well as the occurrence of non-steady and non-sinusoidal grid voltage scenarios, bring complications to microgrid energy management. Consequently, control strategies employed to coordinate DERs in dispatchable microgrids need to be resilient to such non-ideal conditions. Hence, this paper demonstrates that a multi-purpose strategy, so-called the Generalized Current-Based Control (GCBC) approach, is capable of steering DERs under such adverse operational scenarios, ensuring proportional current sharing among them while also regulating the microgrid power dispatchability at the PCC. The discussions are supported by an extensive experimental validation on a laboratory-scale single-phase microgrid prototype, demonstrating that the GCBC approach allows DERs of different operational natures to be coordinated, respecting their power ratings, and allowing the single-controllable microgrid to endure operation under distorted voltages and support voltage ride-through conditions.
Keywords: Current sharing; Dispatchable microgrid; Distorted voltages; Distributed energy resources; Inverters; Power quality; Voltage ride through